Alignment of a 360° image with posed color images for locally accurate texturing of 3D mesh - Khanal, Bishwash; Om, Madhav; Rijal, Sanjay; Ojha, Vaghawan Prasad (Frontiers in Computer Science, 2024)
With the popularity of 3D content like virtual tours, the challenges of 3D data registration have become increasingly significant. Registration of heterogeneous data obtained from 2D and 3D sensors is required to create photo-realistic 3D models. However, the alignment of 2D images with 3D models introduces a significant challenge due to their inherent differences. This paper introduces a rigorous mathematical approach to align a 360 • image with its corresponding 3D model generated from images with known camera poses followed by texture projection on the model. We use SIFT feature descriptors enhanced with a homography-based metric to establish correspondences between the faces of a cubemap and the posed images. To achieve optimal alignment, we use a nonlinear least squares optimization technique with a custom objective function. Subsequently, the outcomes of the alignment process are evaluated through texturing using a customized raytracing algorithm. The resulting projections are compared against the original textures, with a comprehensive assessment of the alignment's fidelity and precision.